Evolution of dynamics of omni-channel pre-sale and spot competition based on consumer heterogeneity. Issue 1 (January 2021) - Li, Peiqin
Abstract: The paper constructs the pre-sale competition model, the pre-sale and spot hybrid competition model, and the pure spot competition model under the influence of the pre-sale promotion efforts. In the analysis of complete pre-sale competition model, only when the homogeneity of consumers is high, retailers will launch full pre-sale competition. If the pre-sale competition is to be launched, the greater the difference in the response of consumers' demand to the pre-sale promotion, the higher the requirement for the homogeneity of consumers is. In the hybrid competition model of presale and spot, it is found that the optimal price equilibrium solution to full pre-sale competition is always less than the optimal price equilibrium solution of both pre-sale market and spot market. In the pure spot market competition model, the conditions are given for breaking the hybrid competition equilibrium between pre-sale and spot market, so as to realize the pure spot market competition. Finally, the paper finds the consumer heterogeneity interval optimized by the above three models through numerical analysis. And when heterogeneity of consumers in a medium range, enterprises 1 need more significant effort level to achieve the established earnings rise, on the other hand, when a consumer heterogeneity, within the range of low or high level interval, enterprise 1 only takes significant promotional effort in general level, the rise of yield can be achieved.